VOLUME 151, SUPPLEMENT 1: 57th Pharmacological Days - and Slovak Pharmacological Meeting, Czech (Biomedical papers, 2007)
The Supplement 1 of Biomedical Papers, Vol. 151 (2007) contains contributions presented at the 57th PharmacologicalDays, in other words, at the 57th Czech and Slovak Pharmacological Meeting. This meeting takes place in Olomouc,on September 12-14, 2007.Palacky University at Olomouc is pleased to host this event which represents a traditional gathering of pharmacologists,toxicologists and scientists interested in fi elds overlapping with these two broadly defi ned fi elds of biomedicalsciences. It is also a good tradition that this meeting is a truly Czecho-Slovakian one with participants coming fromboth sides of the friendly borders between Czech and Slovak Republics.Olomouc is, in many aspects, an almost ideal place for meetings of scientifi c communities. It is a city with thesecond oldest University in the Czech Republic (after Charles University of Prague), founded in 1573 which is alsoknown for their famous former students, e.g. Albrecht Eusebius Valdstejn (Wallenstein) or Gregor Mendel. Its location,not much distant from Prague, Bratislava, Cracow, Vienna or Budapest makes Olomouc a lively city full of studentsand scholars coming from all places of the world.We believe that the 57th Pharmacological Days will off er a good opportunity for mutual exchange of ideas and formeeting of friends and coworkers.
Keywords: 57th Pharmacological Days